Density-functional tight-binding modeling of electromechanics of phosphorene - Pihlajamäki, Antti (2018)
Single-layer black phosphorus or phosphorene is a two-dimensional material made from a puckered honeycomb structure. It is a semiconductor with a tunable band gap and both its mechanical and electronic properties are highly asymmetric because of the puckering. Recently there has been numerous computational studies and some experimental works trying to bring deeper understanding about this relatively new 2D material. In this study we simulate phosphorene using computationally low-cost density functional tight-binding (DFTB) method to see how stretching, shearing and bending affect its electronic properties. The band structure analysis shows that there is a relation between shearing and bending. This discovery is a confirmation for the relation between earlier theoretical predictions concerning bending and the computational results about shearing.